ANALISIS PASANG SURUT PERAIRAN MUARA SUNGAI MESJID DUMAI - Musrifin, Musrifin (Jurnal Perikanan dan Kelautan, 2011)
Tidal analyze have been conducted at Sungai Mesjid Estuary by the end of 2007. Fortnightly tidal range was measured by peil-schall. Harmonic Admiraltyanalyze was applied to find out the Formzahl number. Average tidal range was 2,3meter, mean low water level (MLWL) 0,39 meters and mean high water level(MHWL) was 2,7 meters. Based on Formzahl number F = 0,43 the type of tidal ismixed predominantly semidiurnal. Flood and ebb tide occur twice a day where onetidal range is different in height from the other.